Initial experience with the novel EmboTrap II clot-retrieving device for the treatment of ischaemic stroke. Issue 3 (June 2019) - Valente, Iacopo; Nappini, Sergio; Renieri, Leonardo; Pedicelli, Alessandro; Lozupone, Emilio; Colosimo, Cesare; Mangiafico, Salvatore; Limbucci, Nicola
Introduction: We report our experience with the novel stent-type clot-retrieval device EmboTrap II for the revascularization of large artery occlusions in acute ischaemic stroke. Materials and methods: Twenty-nine patients with acute ischaemic stroke due to large artery occlusion underwent mechanical thrombectomy with the new EmboTrap II in two Italian centres. Clinical, procedural and radiological data were collected. Angiographic results and neurological outcomes were analysed. Results: Only large vessel occlusions were included. Intravenous thrombolysis was administered in 72% of patients. Successful reperfusion (TICI 2b-3) was obtained in 76% of patients treated exclusively with EmboTrap II. No device-related permanent complications occurred. Conclusion: In our experience, mechanical thrombectomy with EmboTrap II is safe and effective. Reperfusion rate was comparable to that obtained with other stent retrievers.